Adding Value to Tilapia Production and Creating Product Recognition by Tilapia Business Cooperation Network, Phayao Province - Srepirote, Kittisak; Ratanasanguanvongs , Kamolpong; Buntavong, Burin (Area Based Development Research Journal, 2023)
Ban Tam Sub-district, Phayao Province of Thailand is a fishing community area. Farmers have formed a cooperative called "Ban Tam Tilapia Cooperative" with 90 members, and their average daily production capacity is 5 tons. However, they face marketing challenges, particularly in terms of pricing and dealing with middlemen in the fish trade. To address these issues and enhance tilapia production and awareness, a research study used online surveys to assess consumer perceptions. The collaborative network of the tilapia business enterprise include the Ban Tam Tilapia Cooperative, fish farmers, restaurant owners, and tilapia consumers. The study found that consumers who are interested in and purchase tilapia base their decisions on the quality of the fish. The strategies for enhancing value to tilapia production and creating product awareness through the collaborative network of tilapia business enterprises are 1) Establishing a network for operations, 2) Increasing the value of tilapia through processing and involving farmers in the process, 3) Designing product label and quality certification symbol Phayao tilapia, and 4) Creating awareness through using media and communication technology results in collaboration in tilapia business. As follows, the Ban Tam Tilapia Cooperative produces fresh tilapia products, trimmed into pieces, and packaged. They also produce frozen tilapia products. The brand logo is "Nil Phayao Chumpathong" and the product brand is "Pla-Tam." Marketing channels and online distribution channels are used. Restaurant operators have tilapia dishes on their menus. As a result, the cooperative can sell tilapia at 60 Baht, up from 52 Baht, and increase their income by 36,000 Baht (about 1,025 US dollars) per production cycle.